Combining different types of data in studying attitudes to English as a Lingua Franca - Stanojević, Mateusz-Milan (Array, 2012)
This paper deals with the attitudes of Croatian speakers to ELF, in particular to its pronunciation. Four methods were combined to reach conclusions about the status of ELF in Croatia: diary study, teacher interviews, a preliminary focus group interview and a survey. Whilst the first three methods revealed that the subjects regularly disfavour ‘bad pronunciation’, the survey showed that when it actually comes to talking to either native or non-native speakers, the subjects turned out to be tolerant to a slight accent. This clearly suggests a case of what is known as linguistic schizophrenia (B.B. Kachru 1977 ; Seidlhofer 2001). However, there are notable differences among groups of participants depending on variables such as professional profile, gender, degree of ease and success in learning pronunciation, and national pride. In any case, the combination of these methods proved to be a very good way to deal with the topic. The diary study is a valuable method to look into everyday practices and can feed nicely into survey questions. The preliminary survey highlighted the importance of different groups of participants and the need for groups of questions focusing around different factors. The preliminary focus group interview showed that it is crucial to have a single homogenous group of participants, as well as a trained facilitator. Finally, teacher interviews pointed to the possibility of similar attitudes being held by university teachers and the students they teach, which suggests that attitudes may be perpetuated. Overall, triangulation across methods and participants in the way proposed in the present paper provided a wealth of data, allowing a bottom-up view and a top-down view on the state of ELF in Croatia.